The role of brain-localized gamma and alpha oscillations in inattentional deafness: implications for understanding human attention - Callan, Daniel E.; Fukada, Takashi; Dehais, Frédéric; Ishii, Shin (Frontiers in Human Neuroscience, 2023)
The processes involved in how the attention system selectively focuses on perceptual and motor aspects related to a specific task, while suppressing features of other tasks and/or objects in the environment, are of considerable interest for cognitive neuroscience. The goal of this experiment is to investigate neural processes involved in selective attention and performance under multi-task situations. Several studies have suggested that attention-related gamma band activity facilitates processing in task-specific modalities, while alpha band activity inhibits processing in non-task-related modalities. However, investigations into the phenomenon of inattentional deafness/blindness (inability to observe stimuli in non-dominant task when primary task is demanding) have yet to observe gamma band activity. This EEG experiment utilizes an engaging whole-body perceptual motor task while carrying out a secondary auditory detection task to investigate neural correlates of inattentional deafness in natural immersive high workload conditions. Differences between hits and misses on the auditory detection task in the gamma (30 to 50 Hz) and alpha frequency (8 to 12 Hz) range were carried out at the cortical source level using LORETA. Participant auditory task performance correlated with an increase in gamma band activity for hits over misses pre- and post- stimulus in left auditory processing regions. Alpha band activity was greater for misses relative to hits in right auditory processing regions pre- and post- stimulus onset. These results are consistent with the faciliatory/inhibitory role of gamma/alpha band activity for neural processing. Additional gamma and alpha band activity was found in frontal and parietal brain regions thought to reflect various attentional monitoring, selection, and switching processes. The results of this study help to elucidate the role of gamma and alpha frequency bands in frontal and modality specific regions involved with selective attention in multi-task immersive situations.